Pathologic and gene expression features of metastatic melanomas to the brain. Issue 15 (21st May 2013) - Hamilton, Ronald; Krauze, Michal; Romkes, Marjorie; Omolo, Bernard; Konstantinopoulos, Panagiotis; Reinhart, Todd; Harasymczuk, Malgorzata; Wang, YangYang; Lin, Yan; Ferrone, Soldano; Whiteside, Theresa; Bortoluzzi, Stephanie; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND The prognosis of metastatic melanomas to the brain (MBM) is variable with prolonged survival in a subset. It is unclear whether MBM differ from extracranial metastases (EcM) and primary melanomas (PrM). METHODS To study the biology of MBM, histopathologic analysis of tumor blocks from patients' craniotomy samples and whole‐genome expression profiling (WGEP) with confirmatory immunohistochemistry were performed. RESULTS High mononuclear infiltrate and low intratumoral hemorrhage were associated with prolonged overall survival (OS). Pathway analysis of WGEP data from 29 such craniotomy tumor blocks demonstrated that several immune‐related BioCarta gene sets were associated with prolonged OS. WGEP analysis of MBM in comparison with same‐patient EcM and PrM showed that MBM and EcM were similar, but both differ significantly from PrM. Immunohistochemical analysis revealed that peritumoral CD3+ and CD8+ cells were associated with prolonged OS. CONCLUSIONS MBMs are more similar to EcM compared with PrM. Immune infiltrate is a favorable prognostic factor for MBM. Cancer 2013;119:2737–2746. © 2013 American Cancer Society.